DERIVATIONAL TENDENCIES IN COMMUNICATIVE PHRASEOLOGICAL UNITS (Archive of Conferences, 2021)
The paper is dedicated to my teacher, to the outstanding linguist Alexander V. Kunin who introduced a most productive phraseological conception and an original method of phraseological identification that was first formulated in his doctoral thesis in the early sixties1 and developed and modified in the scholar’s later books. Alexander V. Kunin contributed greatly to the whole theory of phraseology